La filosofía de lo implícito de Eugene Gendlin - Barceló, Tomeu (Miscelánea Comillas, 2008)
This article outlines the connections between the philosophical system of Gendlin, philosopher, psychotherapist and the creator of focusing, with the perennial philosophy postulates. It also presents the closest philosophical and psychological antecedents that shaped the Gendlin’s system: phenomenology, existentialism and Carl R. Roger’s contributions. It finally establishes resemblances between the postulates of the Philosophy of the Implicit and some newer hypothesis of the contemporary science.